Design of a Compact and Versatile Bench Scale Tubular Reactor - Ram Prasad; Gaurav Rattan (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2009)
A compact and versatile laboratory tubular reactor has been designed and fabricated keeping in view of reducing capital cost and minimising energy consumption for gas/vapor-phase heterogeneous catalytic reactions. The reactor is consisted of two coaxial corning glass tubes with a helical coil of glass tube in between the coaxial tubes serving as vaporiser and pre-heater, the catalyst bed is in the inner tube. A schematic diagram of the reactor with detailed dimensions and working principles are described. The attractive feature of the reactor is that the vaporiser, pre-heater and fixed bed reactor are merged in a single compact unit. Thus, the unit minimises separate vaporiser and pre-heater, also avoids separate furnaces used for them and eliminate auxiliary instrumentation such as temperature controller etc. To demonstrate the system operation and illustrate the key features, catalyst screening data and the efficient collection of complete, and accurate intrinsic kinetic data are provided for oxidation of CO over copper chromite catalyst. CO oxidation is an important reaction for auto-exhaust pollution control. The suitability of the versatile nature of the reactor has been ascertained for catalytic reactions where either volatile or vaporizable feeds can be introduced to the reaction zone, e.g. oxidation of iso-octane, reduction of nitric oxide, dehydrogenation of methanol, ethanol and iso-propanol, hydrogenation of nitrobenzene to aniline, etc. © 2009 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0)